Iatrogenic Acute Aortic Dissection in the Era of Minimally Invasive Cardiac Surgery - Experience of a Center and Review of Literature - Viti,Daniele De (2021)
Abstract Introduction: Iatrogenic acute aortic dissection (IAAD) type A is a rare but potentially fatal complication of cardiac surgery. Methods: The purpose of this article is to review the literature since the first reports of IAAD in 1978, examining its clinical characteristics and describing operative details and surgical outcomes. Moreover, we reviewed the recent literature to identify current trends and risk factors for IAAD in minimally invasive cardiac surgery procedures, often related to femoral artery cannulation for retrograde perfusion. Results: We found that IAAD ranges from 0.04 to 0.29% of cardiac patients in overall trials and ranged from 0.12 to 0.16% between 1978-1990, before the minimally invasive surgical era. And we concluded that since the first cases to the recent reports, the incidence of IAAD has not significantly changed. As minimally invasive procedures are on the rise, some authors think that the incidence of IAAD could increase in the future; we think that using all the precaution - such a strict monitoring of perfusion pressure throughout the intervention, avoiding extremely high jet pressures using vasodilators, repositioning of arterial cannula, or splitting perfusion in both femoral arteries -, this complication can be extremely reduced. Finally, we describe a very singular case occurring during mitral valve replacement followed by spontaneous dissection of left anterior descending artery one month later. Conclusion: The present article adds to the literature a more detailed clinical picture of this entity, including patients' characteristics, the mechanism, timing, and localization of the tear, and mortality details.